Analisis Kesejahteraan Petani Karet Desa Payaombik Padang Lawas Utara Melalui Pendekatan Maqashid Syariah - Restu Amelia Rambe; Nurul Jannah; Agwa Naser Daulay (Universitas Mataram, 2023)
This research is intended to analyze the welfare of rubber farmers in Payaombik village, Dolok subdistrict, North Padang Lawas district. Using descriptive qualitative research methods. The results of the research show that: 1.) the welfare of rubber farmers includes, a) maintaining religion by strengthening religious understanding, carrying out the five daily prayers, fasting in the month of Ramadha, giving zakat and performing the Hajj. b) protecting the soul is done by dressing simply, assessing the family's food needs, and repairing the house. c) maintaining reason (hifz aql) is done like farming, looking after ducks, listening to lectures. And stay away from drugs and alcohol. d) looking after offspring, such as guiding children and taking them to boarding schools, higher education studies and maintaining their health. And also monitor for deviant behavior. e) guarding assets such as buying rice fields, and livestock ducks, and alms for building mosques, and also not going on extravagances, and avoiding haram capital (money from gambling) for agriculture The income of farming families from the rubber farming business they own is for farmers with a land area of ​​3 ha reaching an average income of between IDR 600,00,- to IDR 650,000,- per week. Likewise, rubber farmers who have a land area of ​​2 ha achieve an average income of IDR 450,000 - 500,000 per week. Likewise, rubber farmers who have a land area of ​​1 ha achieve an average income of between Rp. 400,000,- to Rp. 420,000,- per week from their rubber production.